How Consumers Accept Unmanned Smart Stores? – Introducing a Proposed Technology Acceptance Model - Eszter Szabó-Szentgróti; Márta Konczos-Szombathelyi; Szabolcs Rámháp; Petra Kinga Kézai (Chemical Engineering Transactions, 2023)
Digitalization and technological innovation have revolutionized the retail sector. In recent years, a new trend has emerged in the form of unmanned stores, pioneered by Amazon Go. Unmanned solutions using artificial intelligence are beginning to enter the public consciousness and represent a new sustainability perspective (such as lowering paper waste, packaging or using sustainable construction materials) in trade. Although it is not yet widespread and is still a new solution for consumers, the global market dynamics suggest that it will expand in the future. Unmanned shops pose some challenges, but these can be effectively addressed by the appropriate introduction of new technology. To identify or filter out potential shortcomings of this technology on the consumer side, it is also necessary to examine the acceptance of this technology by customers. In this paper, the internationally accepted Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model was modified and used to examine how consumers accept this technology. For data analysis, Partial Least Squares-Structural Equation Modelling method was applied. In the proposed model six constructs were examined on how they influence the intention to use. In the performed query, Hungarian university students’ behavioural intention is influenced by performance expectancy, effort expectancy, and hedonic motivation. However social influence, atmosphere, and price sensitivity have no significant influence on use intention.